The Influence-Network Model of the Photojournalistic Icon. (December 2018) - Dahmen, Nicole Smith; Mielczarek, Natalia; Perlmutter, David D.
Iconic images are those that rise to the forefront of our collective, visual public consciousness to become the defining, enduring image of an event: a naked Vietnamese girl screaming out in pain following a napalm attack, U.S. Marines raising the American flag at Iwo Jima, and a German dirigible engulfed in flames and falling to the ground. Iconic images have a discursive value that helps citizens navigate and understand the political and social contexts of complex events. Traditionally, news photographs became iconic largely through their prominent placement on the front pages of elite newspapers across the globe. But, undeniably, in the age of digital news, mobile phones/tablets, and social media, the media component has changed the equation for the formation of iconic imagery and collective visual consciousness. With the speed, ease of access, and abundance of information sources available in the current age, a volume of images can now represent a significant (or not so significant) event. This monograph traces the development of iconic image literature and then proposes a model termed the "influence-network model of the photojournalistic icon, " which predicts how photographs of events become iconic (or not).